Answer:
0 8 + 3
hope this is right if not im so sorry
A few years ago, a country consumed 19,400,000 barrels of oil per day. That same year, there were about 119,000,000 households in that country. A barrel of oil is 42 U.S. gallons. Estimate how many gallons each household in the country consumed each day that year by rounding down all three numbers. (Round 19,400,000 barrels to 19,000,000 barrels, 119,000,000 households to 115,000,000 households, and 42 gallons to 40 gallons. Round your answer to two decimal places.)
_________ gal/household/day
Calculate the answer without using estimation and compare the two results. (Round your answer to two decimal places.)
___________gal/household/day
Following are the calculation to fill in the blank:
For Part a)
Each home in this town consumed
[tex]\to 40 \times \frac{19000000}{115000000}\\\\\to 40 \times \frac{19}{115}\\\\\to 40 \times 0.165\\\\\to 6.6 \ \text{gallons of oil per day}[/tex]
For Part b)
Without completing the sentence,
[tex]\text{Total consumption = 19200000 barrels}\\\\\text{Total number of households = 118000000}[/tex]
As a result, each household consumed.
[tex]\to \frac{19200000}{118000000} \\\\\to \frac{192}{1180} \ (barrels)\\\\[/tex]
In the given scenario, each barrel includes 42 gallons of oil. Therefore, every household consumed [tex]42 \times \frac{192}{1180} = 6.83 \ gallons[/tex] oil each day.
Learn more:
brainly.com/question/14798687
Hence, each household will consume 6.60 gallons per day.
Total Households of that country =115000000 (approx.)
Total barrels used per day =19000000 (approx.)
Given 1 barrel = 40 gallons (approx.)
So total gallons used per day = 19000000 x 40 =760000000
So each household will consume gallons per day = total gallons used per day / Total household of that country
=[tex]=\frac{760000000}{ 11500000}[/tex]
=6.60 gallons/household/day
So each household will consume 6.60 gallons per day.
Learn More: https://brainly.com/question/12272570
What is the equation in slope-intercept form of a line with slope of 5 and y-intercept of 3?
y=5x+3
Because the starting value(y intercept is 3) and the slope(x) is 5
please help as soon as possible
I WILL MARK YOU AS BRAINLIEST
Answer:
Last choice
Step-by-step explanation: Subtract 11 and then divide by 3. A would be greater than -2 and last choice shows that
Is the relation a function?
{(-6, -1), (5,-1), (0, -1), (-2, -1), (3, -1)}
Answer:
yes it is a function
Step-by-step explanation:
For that no two x values are the same with different y values
00:00
Brice is finding the sum of 468 and 241 by breaking it into smaller problems
He uses place value and finds the sums of the hundreds, tens, and ones.
What is the sum of the tens? Enter your answer in the box.
1
evaluate the following expression -7x(7+9)
Answer:
-112
Step-by-step explanation:
Add
-7(7+9)
Multiply
-7x16
Wallah! You have the answer
-112
[tex]\text{Simplify the expression:}\\\\-7x(7+9)\\\\\text{Use the distributive property}\\\\-49x-63x\\\\\text{Combine like terms}\\\\\boxed{-112x}[/tex]
BEST ANSWER GETS TO CHOOSE BRAINLESST OR FOLLOW!
Answer:13 is>
14 is =
15 is >
16 is<
17 is<
18 is =
Step-by-step explanation:
I just know plz mark brainliest
Find the value of x in the triangle pair below
Answer:
x=16.97056274... or 12[tex]\sqrt{2}[/tex]
Step-by-step explanation:
the hypotenuse of a 45, 45, 90 triangle is the length of the leg times the square root of 2
Which equation represents a line parallel to the line whose equations is -2x + 3y =
-4 and passes through the point (1,3)?
Answer:
2. y - 3 = 2/3 (x - 1).
Step-by-step explanation:
-2x + 3y = -4
3y = 2x - 4
y = 2/3 x - 4/3 - so the slope is 2/3.
The slope of a line parallel to it is also 2/3.
It also passes through the point (1, 3).
Using the point-slope form of a line:
y - y1 = m(x - x1) where m = the slope and (x1, y1) is a point on the line, we have:
y - 3 = 2/3 (x - 1) <--- is the required equation.
Answer:
2
Step-by-step explanation:
parallel lines have same slope with different intercept
y= mx+b
m is going to be same with different b
so the given function is:
-2x+3y=-43y= 2x-4y= 2/3x - 4/3Given options:
1. y-3= - 2/3(x-1) ⇒ y= -2/3x +3 + 2/3 ⇒ y= -2/3x +11/3
it has different slope, so is not parallel2. y-3= 2/3(x-1) ⇒ y= 2/3x+3-2/3 ⇒ y= 2/3x + 7/3
it has same slope, so is parallelit should be passing through point (1,3)3= 2/3+7/3 ⇒ 3=3, yes it does3. y-3= -2/3(x+1) ⇒ y= - 2/3x +3- 2/3 ⇒ y= -2/3x + 7/3
it has different slope, is not parallel4. y-3= 2/3(x+1) ⇒ y= 2/3x +3+ 2/3 ⇒ y= 2/3x +11/3
it has same slope, so is parallelit should be passing through point (1,3)3= 2/3+11/3 ⇒ 3≠13/3, no it doesn'ta) the quadratic x^2-4x-21 can be written in the form (x+a)^2+b find the values of and and b
b) hence, or otherwise, solve the equation x^2-4x-21=0
Jake is earning money for a new TV. So far, he has put $54.29, $87.20, and $21.44 into his savings account. How much money has Jake saved?
add all the values together
54.29+87.20=141.49
141.49+21.44=162.93
Answer:
$162.93
Step-by-step explanation:
Do 54.29 + 87.20 + 21.44 and get 162.93 than put this $ in front of you answer then you have $162.93
If f(x) = 2x + 1 and g(x) = x-2 what is the value of f(g(f(3)))? This is so confusing plz help me will mark brainliest A) 1 B) 3 C) 5 D) 7 E) 11
Answer:
11
Step-by-step explanation:
f(3) = 2*3+1 = 6+1 = 7
Then find g(7)
g(7) = 7-2 = 5
Then find f(5)
f(5) = 2*5 +1 = 10+1 = 11
f(g(f(3))) = 11
Answer:
11
Step-by-step explanation:
f(x)=2x + 1
f(3)= 2.3 + 1
f(3)=7
f(g(f(3))) = f(g(7))
Now, we have to find g(7)
g(x)=x -2
g(7)= 7 -2
g(7)=5
f(g(f(3))) = f(g(7)) = f(5)
now we have to find f(5)
f(x)=2x + 1
f(5)=2.5 + 1
f(5)=11
Hope this helps ^-^
Line I and h intersect at what point
Answer:
please show where the lines are graphed in a picture
Step-by-step explanation:
Helppppp meeeee answer thissssssss
Answer:
(-1.025)^3 x (-1.025)^2=(- 1.025)^5
(-y)^3 x (-y)^2 x (-y)= y^6
5= odd, - stays
6= even, - becomes +
Answer:
5) (-1.025)^3* (-1.025)^2 = (-1.025)^5 = (-41/40)^5
10) -y^3 * -y^2 * -y
Multiplying an odd number of negative terms makes the product negative
= - y^3 * y^2 * y
= - y^6
[tex]( {2}^{ - 1} + {3}^{ - 1} )^{2} [/tex]
solve.
will give the brainliest
Answer:
25/36
Step-by-step explanation:
(2^-1 + 3^-1)^2
➡
➡
(1/2 + 1/3)^2
➡
(5/6)^2 = 25/36
Tiffany cells 2 kinds of homemade tomato sauce
Answer:
b
Step-by-step explanation:
Let x represent the number of quarts of Tuscan sauce and
y represents the number of quarts of marinara sauce Tiffany makes.
A quart of Tuscan sauce requires 6 tomatoes and 1 cup of oil
x quarts requires 6x tomatoes and 1x cups of oil
A quart of her marinara sauce requires 5 tomatoes and 1.25 cups of oil
y quarts requires 5y tomatoes and 1.25 y cups of oil
She has 45 tomatoes and 10 cups of oil on hand.
So the constraints are
6x+5y≤45
1x+1.25y≤10
x>=0 and y>=0
After drawing a diagram of what's required to make 1 quart of Tuscan and 1 quart of Marinara sauce, you can more clearly choose answer choice (B) 6x + 5y < (or equal to) 45, x + 5/4y < (or equal to) 10, x>(or equal to)0, y>(or equal to)0.
please mark brainliest :)
Find the solution(s) to x^2- 14x + 49 = 0.
O A. x=-2 and x = 7
B. x= -1 and x = 14
C. x= 7 only
D. x = 7 and x = -7
Answer:
[tex] \boxed{C. \: x = 7 \: only} [/tex]
Step-by-step explanation:
[tex] = > {x}^{2} - 14x + 49 = 0 \\ \\ = > {x}^{2} - (7 + 7)x + 49 = 0 \\ \\ = > {x}^{2} - 7x - 7x + 49 = 0 \\ \\ = > x(x - 7) - 7(x - 7) = 0 \\ \\ = > (x - 7)(x - 7) = 0 \\ \\ = > {(x - 7)}^{2} = 0 \\ \\ = > x - 7 = 0 \\ \\ = > x = 7[/tex]
I need help with is question ASAP please
The y-intercept looks like it's 0 and the slop looks like 6/2 or 3 or maybe 7/2
A new car is purchased for 23400 dollars. The value of the car depreciates at 11.5% per year. To the nearest year, how long will it be until the value of the car is 12700 dollars?
Answer: 5 years
Step-by-step explanation:
Using same formula as for Compound Interest:
12700 = 23400 (1-.115)^t
12700 = 23400 x 0.885^t
0.885^t = 127/234
Convert decimal into fraction:
177/200^t = 127/234
Take logarithm of both sides of thr equation:
t = log 177/200 (127/234)
t = 5.00242
HELP ASAP it says my questions should be at least 20 characters long so what I’m saying right now doesn’t mean anything.
Answer: See pic above for answer. I got it from Photomath
Plz put brainliest
Micheal has 1/2 of a yard of fabric to make book covers. Each book cover is made from 1/8 of a yard of fabric. How many book covers can Micheal make?
Answer:
4
Step-by-step explanation:
[tex]\frac{1}{2}[/tex] ÷ [tex]\frac{1}{8}[/tex] = 4
What is the midpoint of the segment below? (2,3)(-3,-2)
Answer:
(-0.5, 0.5)
Step-by-step explanation:
If those two points are endpoints, just use the midpoint formula.
(-0.5, 0.5)
Answer:
(-1/2,1/2)
Step-by-step explanation:
To find the midpoint, add the x coordinates and divide by 2
(2+-3)/2 = -1/2
add the y coordinates and divide by 2
(3+-2)/2 = 1/2
The midpoint is (-1/2,1/2)
A. 256
B. 265
C. 297
D. 279
Answer:
A.
Step-by-step explanation:
So calculate one of the triangles.
[tex]\frac{12*8}{2} =48[/tex]
48 * 4 = 192
192 + 64 = 256
PLEASE HELP WILL GIVE BRAINLIEST AND 20 POINTS
solve this system of equations
3y-5x=12
y=1/3x
Answer:
x=-3
y=-1
(-3,-1)
Answer:
(-3, -1).
Step-by-step explanation:
I have attached the work to your problem.
Please see the attachment below.
I hope this helps!
14. Roger is on a playground swing, and he is swinging back and forth in such a way that the height, h, in feet, of the swing off the ground is given by the equation h=3cos(3π/2t) +5, where t is in seconds. How many seconds elapses between two consecutive times that the swing is at its maximum height?
Answer:
The time [tex]t = \frac{3}{2}[/tex] seconds elapses between two consecutive times that the swing is at its maximum height 'h' = 2
Step-by-step explanation:
Explanation:-
Step(i):-
Given function [tex]h(t) = 3 cos (\frac{3\pi }{2 t} ) +5[/tex] ....(i)
By using derivative formulas
[tex]\frac{d cosx }{d x} = -sinx[/tex]
[tex]\frac{d x^{n} }{d x} = n x^{n-1}[/tex]
[tex]\frac{d t^{-1} }{d x} = -1 t^{-1-1} = - t^{-2} = \frac{-1}{t^{2} }[/tex]
Step(ii):-
Differentiating equation(i) with respective to 't'
[tex]h^{l} (t) = 3(-sin(\frac{3\pi }{2t})\frac{d}{dt} (\frac{3\pi }{2t } )+0[/tex] ...(ii)
[tex]h^{l} (t) = 3(-sin(\frac{3\pi }{2t})(\frac{-3\pi }{2t^{2} } )+0[/tex]
Equating zero
[tex]h^{l} (t) = 3(-sin(\frac{3\pi }{2t})(\frac{-3\pi }{2t^{2} } )=0[/tex]
[tex]3(-sin(\frac{3\pi }{2t})(\frac{-3\pi }{2t^{2} } ) = 0[/tex]
on simplification , we get
[tex](sin(\frac{3\pi }{2t}) = 0[/tex]
now we use formulas
sin 0 = 0 and sinπ = 0
General solution
[tex](sin(\frac{3\pi }{2t}) = sin\pi[/tex]
[tex](\frac{3\pi }{2t}) = \pi[/tex]
Cancellation 'π' on both sides, we get
[tex]3 = 2 t[/tex]
Dividing '2' on both sides , we get
[tex]t = \frac{3}{2}[/tex]
Again differentiating with respective to 't' , we get
[tex]h^{ll} (t) = 3(-cos(\frac{3\pi }{2t})(\frac{-3\pi }{2t^{2} } )+ (-3)(-sin(\frac{3\pi }{2t} )(\frac{6\pi }{2t^{3} }[/tex]
Put t= 3/2 and simplification
[tex]h^{ll} (t) < 0[/tex]
The maximum height
[tex]h(t) = 3 cos (\frac{3\pi }{2 t} ) +5[/tex]
[tex]h(\frac{3}{2} ) = 3 cos (\frac{3\pi }{2(\frac{3}{2} )} )+5[/tex]
[tex]h(\frac{3}{2} ) = 3 cos (\pi )+5 = -3+5 =2[/tex]
[tex]t = \frac{3}{2}[/tex] seconds elapses between two consecutive times that the swing is at its maximum height 'h' = 2
Conclusion:-
The time [tex]t = \frac{3}{2}[/tex] seconds elapses between two consecutive times that the swing is at its maximum height 'h' = 2
Please Help me it’s geometry
Answer:
Option C.
Step-by-step explanation:
Given: In [tex]\Delta OPQ,m\angle O=107^{\circ},m\angle P=28^{\circ} [/tex].
In [tex]\Delta OPQ[/tex],
[tex]m\angle O+m\angle P+m\angle Q=180^{\circ}[/tex] (Angle sum property)
[tex]107^{\circ}+28^{\circ}+m\angle Q=180^{\circ}[/tex]
[tex]135^{\circ}+m\angle Q=180^{\circ}[/tex]
[tex]m\angle Q=180^{\circ}-135^{\circ}[/tex]
[tex]m\angle Q=45^{\circ}[/tex]
Now,
[tex]m\angle O>m\angle Q>m\angle P[/tex]
In a triangle, the greatest angle has largest opposite side and smallest angle has smallest opposite side. So, we conclude that
[tex]PQ>OP>QO[/tex]
Therefore, the correct option is C.
If g(x) = -4x + 5, find g(2x-1).
Answer:
- 8x + 9
Step-by-step explanation:
To evaluate g(2x - 1) substitute x = 2x - 1 into g(x), that is
g(2x - 1)
= - 4(2x - 1) + 5 ← distribute parenthesis and simplify
= - 8x + 4 + 5
= - 8x + 9
Answer:
= - 8x + 9
Step-by-step explanation:
= - 8x + 4 + 5
= - 8x + 9
Pls help me on this................
Answer:
Step-by-step explanation:
Becky made 4 quarts of chicken noodle soup in a big pot, then served 112-cup bowls of soup to 6 people. How much soup is left in the pot?
Answer:
1qt 3c
Step-by-step explanation:
What is -6 divided by -1.2?
Answer:
5.
Step-by-step explanation:
This is the same as saying:
-6/(-6/5).
To solve the equation, we multiply by the reciprocal and simplify. In this case, we multiply both sides of the equation by -5/6.
-6 * (-5/6) = 5.
The answer must be positive, as two negatives divided equal a positive.
I hope this helps!
The solution of expression after divide is,
⇒ 5
We have to given that;
⇒ - 6 is divided by - 1.2
Now, We can simplify as,
⇒ - 6 is divided by - 1.2
It can be written as,
⇒ - 6 ÷ - 1.2
⇒ - 6 / - 1.2
⇒ 6 / 1.2
⇒ 60 / 12
⇒ 5
Thus, The solution of expression after divide is,
⇒ 5
Learn more about the divide visit:
https://brainly.com/question/28119824
#SPJ6